2019
DOI: 10.1038/s41598-019-49645-5
|View full text |Cite
|
Sign up to set email alerts
|

C60 ions of 1 MeV are slow but elongate nanoparticles like swift heavy ions of hundreds MeV

Abstract: This study reports that high fluence fullerene ion (C60+) irradiation of 1–6 MeV, which was made possible by a new-type of high-flux ion source, elongates metal nanoparticles (NPs) in amorphous SiO2 as efficiently as swift heavy ions (SHIs) of 200 MeV Xe14+, i.e., two orders of the magnitude higher energy ions. Comparing the irradiation effects induced by both the beams, the stopping processes of C60 ions in SiO2 are discussed in this paper. Despite of having almost the same elongation efficiency, the C60+ irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…The track lengths showed some variation with the mean length of 66.3 nm and the standard deviation of 7.9 nm. While many hillocks were observed in quartz (SiO 2 ) crystal irradiated with the same conditions 20 , the hillocks were not observed in the case of c-Si.…”
Section: Resultsmentioning
confidence: 88%
“…The track lengths showed some variation with the mean length of 66.3 nm and the standard deviation of 7.9 nm. While many hillocks were observed in quartz (SiO 2 ) crystal irradiated with the same conditions 20 , the hillocks were not observed in the case of c-Si.…”
Section: Resultsmentioning
confidence: 88%
“…SHI irradiation causes a peculiar shape transformation induced to nanoparticles (NPs) embedded in amorphous SiO 2 matrices. Numerous experiments [1][2][3][4][5][6][7][8][9][10][11][12] have shown that spherical NPs can become elongated in the ion beam direction and evolve into prolate shapes or rods. While intriguing from an application point of view, the shaping process also offers unique insights into the fundamentals of ion-solid interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 28–30 ] On the one hand, the size, shape, and distribution of NPs could be tailored through the selected implantation conditions (e.g., ion energies, ion fluences, ion species, incident angles) to meet the requirement of practical applications in terms of high integration and high stability. [ 31 ] On the other hand, strong interaction between embedded NPs and surrounding dielectric environment enables enhanced light‐matter effects in a monolithic platform for photonic applications. [ 30,32–36 ] Particularly, for the systems containing dielectrics embedded with NPs, the optical properties and other functionality of dielectrics could be modified by the LSPR effect, and therefore the substrates could be endowed with new features.…”
Section: Introductionmentioning
confidence: 99%